Leap! - Summer, Eric; Fanning, Elle, 1998-; DeHaan, Dane, 1987-; Jepsen, Carly Rae, 1985- (Lions Gate Entertainment, 2017)
An orphan girl dreams of becoming a ballerina and flees her rural Brittany for Paris, where she passes for someone else and accedes to the position of pupil at the Grand Opera house.
Elle Fanning, Dane Dehaan, Carly Rae Jepsen.
Rating: PG; for some impolite humor and action.
DVD, wide screen.
English dialogue; Spanish subtitles; subtitled for the deaf and hard of hearing (SDH).
Keywords: Feature films; Children's films; Video recordings for the hearing impaired